Analysis of the Crime of Hirabah in Islamic Criminal Law and Its Relevance to Modern Crimes - Ana Zuwita; David Akmal Siregar; Intan Tri Annisa Sihite; Fayyadh Azizan Rahman Nst (ISNU Sumatera Utara, 2024)
This study examines the concept of jarimah hirabah in Islamic criminal law and its relevance to modern crimes. The background of this research is based on the increasing occurrence of various contemporary crimes that threaten public security, such as armed robbery, terrorism, and organized crime. This study aims to analyze the concept of hirabah from the perspective of Islamic criminal law and to examine its compatibility with contemporary criminal phenomena. The research employs a normative legal method with a library research approach through the examination of relevant Islamic legal sources, including the Qur’an as the primary normative foundation analyzed through scholarly literature, as well as secondary legal materials in the form of academic journals, books, and relevant previous studies. The data were analyzed using a descriptive qualitative method. The findings indicate that hirabah is one of the hudud offenses characterized by the use of violence or threats of violence committed openly, resulting in fear and disruption of public security. In its development, the concept of hirabah is relevant to several forms of modern crime, including violent theft, terrorism, and organized crime, as these offenses share common elements such as the use of violence, the creation of fear, and disturbances to public order. Nevertheless, not all modern crimes can be classified as hirabah, as they must still fulfill the specific elements prescribed under Islamic criminal law. Therefore, hirabah can be understood as a relevant conceptual framework for analyzing modern crimes that threaten public security.